Measurement of Lead content in Channa striata by using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) - Khairuddin, Khairuddin; Yamin, M.; Kusmiyati, Kusmiyati; Sedijani, Prapti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Research on heavy metals Pb is important to be done to protect consumers from dangerous impact, especially on human beings. The purpose of this study was to determine the Lead (Pb) content in Snakehead fish (Channa striata) taken from Rawa Taliwang Lake. Data collection for the Snakehead fish (Channa striata) species in this study was carried out in water bodies of Taliwang Lake area. There were 2 data collection stations, namely on the east and west parts of the lake. Gill nets were used to catch fish. Fish samples were caught as many as 4 fish for each station. The fish samples were then analyzed at the West Nusa Tenggara Health, Testing, and Calibration Laboratory Center. The data analysis method was carried out by taking muscle tissue from the fish and then analyzing the Pb heavy metal content using an Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). Pb found in Snakehead fish in this research is 0,44 ppm. The benefit of this study is to protect consumers who consume Snakehead fish from Lead heavy metal contaminants. The concentration of Lead in fish tissue was measured after adding concentrated 10 ml HNO3 and 2 ml H2O2 30%. The conclusion of this study is that the heavy metal content of Pb in Channa striata is 0.44 ppm.Reaseach on Pb heavy metal sould be continued in order to protect consumers from metal contamination.